Statistics for Surface Modes of Nanoparticles with Shape Fluctuations (Communications in Computational Physics, 2010)
We develop a numerical method for approximating the surface modes ofsphere-like nanoparticles in the quasi-static limit, based on an expansion of (the angularpart of) the potentials into spherical harmonics. Comparisons of the results obtainedin this manner with exact solutions and with a perturbation ansatz prove thatthe scheme is accurate if the shape deviations from a sphere are not too large. Themethod allows fast calculations for large numbers of particles, and thus to obtain statisticsfor nanoparticles with random shape fluctuations. As an application we presentsome statistics for the distribution of resonances, polariziabilities, and dipole axes forparticles with random perturbations.